Development and Students’ Perception on Teaching Aids of Photoelectric Effect Experiment Using Leds - Hartono Bancong; Ana Dhiqfaini Sultan; Subaer Subaer; Muris Muris (Universitas Muhammadiyah Makassar, 2019)
The photoelectric effect experiment generally uses a very sophisticated and expensive apparatus. Some high schools and even universities in Indonesia cannot afford to conduct this experiment because of the high price of the apparatus. The purpose of this study was to develop a user-friendly, and cost-effective teaching aids which can be used to demonstrate the concepts of modern physics related to the photoelectric effect. The stages of this study employed the Four-D model, namely define, design, develop, and disseminate. Based on experts and practitioner evaluation, the developed teaching aids and practicum devices of photoelectric effect experiment were found to be valid and reliable. The results of the experiment by using this developed teaching aids of the photoelectric effect showed that there is a linear relationship between the stopping potential and the frequency of light emitted by the LED. These results are consistent with Millikan's experimental results, the first physicist who succeed in proving Einstein's hypothesis of the photoelectric effect, that in the photoelectric effect the stopping potential does not depend on the intensity of light but depends only on the frequency of light. In this study, the Planck’s constant value obtained is 6.408x10-34 J.s. Although this value is slightly smaller than the accepted value of Planck's constant that is 6.626x10-34 J.s, it is good enough considering the instrumental error occurred during the measurement of current and voltage. Furthermore, the students’ perception of the developed teaching aids and practicum devices of the photoelectric effects experiment are 74.9% (good) and 80.2% (very good), respectively. This indicates that the photoelectric effect experiment teaching aids and practicum devices that have been developed can be used to demonstrate and prove the concepts of modern physics related to the photoelectric phenomena correctly.Keywords: Teaching Aids, Photoelectric Effect, Students’ Perception